Milk-borne bacterial health hazards in milk produced for commercial purpose in Tigray, northern Ethiopia - Gebretsadik Berhe; Araya Gebreyesus Wasihun; Enquebaher Kassaye; Kibrom Gebreselasie (BMC, 2020)
Abstract Background Milk being a suitable medium for bacterial growth, it can serve as a source of bacterial contamination. Pathogenic bacteria in milk pose a serious health threat to humans and constitute about 90% of all dairy-related diseases. However, there are few studies that examined the health hazards of raw milk consumption in Ethiopia. Therefore, the objective of this study was to assess the prevalence of bacterial contamination and associated factors in milk produced for commercial purpose in Tigray region, northern Ethiopia. Methods This study used a cross-sectional study design, selected 315 persons (168 cafeterias, 96 dairy farms, and 51 milk vendors) for interview and collected the same number of bulk raw milk samples using systematic sampling procedure. Data were collected on socio-demographic, farm hygiene and milk handling practices by trained health professionals. Bacterial contamination was defined as total bacterial count (TBC) > 1 × 105, staphylococcus count (SC) > 105, or coliform count (CC) > 102 CFU/ml by culture and the species of bacteria were determined by standard biochemical tests. Results From the 315 milk samples tested, the prevalence of bacterial contamination was 52% (95% CI: 46.5-57.6). The mean counts of contaminated samples of TBC, SC, and CC were 8.94 ± 0.46 Standard Deviation (SD), 8.52 ± 0.6 SD, and 8.78 ± 0.49 SD log CFU/ml, respectively. The proportion of contamination was significantly lower in milk collected from dairy farms (32/96, 33.3, 95% CI: 24.5-43.2) compared to milk from vendors (33/51, 64.7, 95% CI: 51.4-66.2) and cafeterias (99/168, 58.9, 95% CI, 50.9-76.85). The milk samples were culture-positive for Escherichia coli, Klebsiella pneumoniae, Staphylococcus aureus, K. oxytoca and Citrobacter freundii. Conclusions Over half of the sampled raw milk exhibited bacterial contamination with increasing trend from farmers to points of sale. Thus, milk vendors and cafeteria owners should apply good hygienic and sanitation practices during handling of milk; use appropriate, clean containers, and cold chain during milk transportation; and refrigeration of milk during storage.